EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN INSIDE-OUTSIDE CIRCLE DALAM MENINGKATKAN KEMAMPUAN KOGNITIF MELALUI PEMBELAJARAN IPA PADA SISWA KELAS V - Melinda Rantini; Erwin (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article reports a study that properly proves the effectiveness of the inside- outside circle in improving cognitive abilities through science learning for class V. The researcher used quantitative research. The research method used was quasi-experimental research with a non-equivalent control group design. The data collection technique used was a test instrument with a population of 69 students for classes VA and VB. Related to the results of the pretest, the average value of the experimental class was 68.10 and the control class was 57.33. Based on the posttest results, it was obtained that the average value of the control class was 57.50 and the experimental class was 77.07, which meant that it was 8.97 higher than the control class. It was reinforced by the results of hypothesis testing, the negative rank value of the experimental class learning outcomes was 0.00, which means there was an effect, and the statistical test obtained a significant value of 0.00 < 0.05, which means that there was an improvement. It shows the effectiveness of the application of the IOC in improving cognitive abilities that could be obtained from student learning outcomes.